Dismiss Notice
Join Physics Forums Today!
The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

Cant find the general solution

  1. Apr 15, 2008 #1
    Im looking for a general solution to the following equation but i cant seem to get an answer.
    3xdy = (ln(y[tex]^{6}[/tex]) - 6lnx)ydx

    I've got this far anyway..

    [tex]\frac{3x}{y}[/tex] dy = (ln(y[tex]^{6}[/tex])-ln(x[tex]^{6}[/tex])) dx

    [tex]\frac{dy}{dx}[/tex] = [tex]\frac{y}{3x}[/tex] . 6ln[tex]\frac{y}{x}[/tex]

    [tex]\frac{dy}{dx}[/tex] = [tex]\frac{y}{x}[/tex] . 2ln[tex]\frac{y}{x}[/tex]

    Let z = [tex]\frac{y}{x}[/tex]

    [tex]\frac{dz}{dx}[/tex] = (x[tex]\frac{dy}{dx}[/tex] - y) / x[tex]^{2}[/tex]

    [tex]\frac{dz}{dx}[/tex] = [tex]\frac{1}{x}[/tex]([tex]\frac{y}{x}[/tex] . 2ln[tex]\frac{y}{x}[/tex]) - [tex]\frac{y}{x^2}[/tex]

    z = [tex]\frac{y}{x}[/tex] gives

    [tex]\frac{dz}{dx}[/tex] = [tex]\frac{1}{x}[/tex](2zlnz) - [tex]\frac{z}{x}[/tex]

    [tex]\frac{dz}{dx}[/tex] = [tex]\frac{1}{x}[/tex](2zlnz-z)

    [tex]\frac{dz}{2zlnz - z}[/tex] = [tex]\frac{1}{x}[/tex]dx

    now im stuck...??
  2. jcsd
  3. Apr 15, 2008 #2


    User Avatar
    Science Advisor

    I presume it is the
    [tex]\frac{dz}{2zlnz- z}[/tex]
    that is giving you the problem!

    Write it as
    [tex]\frac{1}{2ln z- 1}\frac{dz}{z}[/tex]
    and let u= 2ln z- 1.
  4. Apr 15, 2008 #3
    Ya, its that part alright!

    Do i write it like [tex]\frac{1}{u}[/tex] [tex]\int[/tex] [tex]\frac{dz}{z}[/tex]?

    [tex]\frac{1}{u}[/tex] [tex]\int[/tex] [tex]\frac{dz}{z}[/tex] = Integral([tex]\frac{dx}{x}[/tex])

    [tex]\frac{1}{u}[/tex] (lnz) = lnx + C

    [tex]\frac{1}{2lnz - 1}[/tex] (lnz) = lnx + C

    Is this right?
    Last edited: Apr 15, 2008
  5. Apr 16, 2008 #4


    User Avatar
    Staff Emeritus
    Science Advisor
    Gold Member

    No. Notice that u is a function of z and is therefore not constant under integration with respect to z. Therefore you need to make a change of variable from [itex]dz\mapsto du[/itex].
  6. Apr 16, 2008 #5



    ([tex]\frac{1}{2}[/tex])lnu=lnx + C

    ln(u)[tex]^{1/2}[/tex] - lnx = C

    ln[[tex]\frac{(u)^{1/2}}{x}[/tex]] = C


    ln[[tex]\frac{(2lnz-1)^{1/2}}{x}[/tex]] = C


    ln[[tex]\frac{(2ln\frac{y}{x}-1)^{1/2}}{x}[/tex]] = C

    [tex]e^{ln[\frac{(2ln\frac{y}{x}-1)^{1/2}}{x}] }[/tex] = [tex]e^C[/tex] , Let [tex]e^C[/tex] = B

    [tex]\frac{(2ln\frac{y}{x}-1)^{1/2}}{x}[/tex] = B

    Am i doing it correctly?
  7. Apr 17, 2008 #6


    User Avatar
    Staff Emeritus
    Science Advisor
    Gold Member

    Looks okay to me :smile:
Know someone interested in this topic? Share this thread via Reddit, Google+, Twitter, or Facebook